Synthesis of 3-(quinolin-2-yl)- and 3,6-bis(quinolin-2-yl)-9H-carbazoles - Li, Yang; Gao, Wentao (Beilstein Journal of Organic Chemistry, 2010)
A simple and efficient synthesis of novel 3-(quinolin-2-yl)- and 3,6-bis(quinolin-2-yl)-9H-carbazoles, utilizing sodium ethoxide as a catalyst via a Friedländer condensation reaction between 3-acetyl-9-ethyl-9H-carbazole or 3,6-diacetyl-9-ethyl-9H-carbazole and β-aminoaldehydes or β-aminoketones is described. All of the title compounds were obtained in good yields of 52–72% and their structures were confirmed by IR, 1H NMR, MS, and elemental analysis.
Keywords: acetylcarbazole; β-aminoaldehyde; β-aminoketone; Friedländer condensation; sodium ethoxide